Labour Taxation – A Comparative Study - Radu, Claudia Florina; Dumiter, Florin; Opreț, Anca Laura (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
In our paper we aim to analyze the tax wedge between labor costs and net wage, this being the main indicator for assessing the tax burden on labor. We analyze the components of the tax wedge and its evolution in time, in the OECD countries and in Romania. In this way we can get an image of the total labor cost, observing that our country belongs to countries where labor taxes have a very high level. Thus, from our analysis we showed that in Romania the tax wedge is around 42%, while the OECD average was only 35.9%. In these circumstances it is necessary to adopt certain measures for shifting the tax burden from labor to other tax bases, with the purpose of a fiscal relaxation of labor income.